(( Technology’s role Time driver Activity-based costing at Provide of information for economic units for customer profitability analysis )) - صحبت حنان; فاضل سهير كاظم (Journal of Economics and Administrative Sciences, 2018)
The economic units always sought to maintain its market position and Trchinh the technology management and modern methods that will support success factors .vdila about it has become a customer and one profitability analysis of the most practical way benefit of economic units as modern management focus their attention on achieving this satisfaction, as the customers make up the axis of the success of every organization and that there are many government units aiming to profit directs attention to customers and the number of these units increased continuously. The administration used the customer profitability analysis in order to obtain information to assist in making and decision-making process. How to use modern techniques and methods to calculate and analyze customer profitability and (TD ABC) as one of modern management accounting techniques that work to help the administration in the financial performance of the company and reduce costs layout. The study aimed to release the cognitive underpinnings of technology on (TD ABC) and the magnitude of the economic advantages of unity and Alatharalamtertbh to use in determining the costs of a major contribution to the rationalization of operational decisions in the production companies. Determine the extent of the possibility of customer profitability analysis when using the method on the basis of cost-oriented time as one of modern management accounting techniques and development activity to the entrance of the cost on the basis of activity and that the application to the General Company for Leather Industries. The study came to a set of conclusions and recommendations, including: - 1. The technique (TDABC) was able to provide for the management of the company known for its customers through a profitability analysis and get a percentage of each group and through these ratios can determine which policies are followed and could be suitable for them. The most important recommendations were: - to maintain the loyalty of customers by providing what fits their desires and what is new and the best quality and the quality and the best prices for them..attention next to the customer profitability analysis, customer interest is also worth being a resource represents an important resource for the company.